Studi Kritis Pembaruan Pendidikan di Minangkabau - Ramadhanul Ikhsan; Nurhapipah; Zulmuqim; Fauza Masyhudi (PT. Banjarese Pacific Indonesia, 2023)
This research aims to describe the thoughts on educational reform by several prominent figures in Minangkabau. These figures are Abdul Karim Amrullah, Abdullah Ahmad, Rahmah El-Yunusiyah, and Sheikh Sulaiman Ar-rasuli. The research method used is the library research research method, library research is research carried out using library literature. The data collection process focuses on collecting various sources and relevant data, scientific literature, and other writings related to thoughts on educational reform in Minangkabau. The results of the research show that there are thoughts about educational reform carried out by several prominent figures in Minangkabau such as Abdul Karim Amrullah, Abdullah Ahmad, Rahmah El-Yunusiyah, and Sheikh Sulaiman Ar-rasuli. The results of the thinking of these figures were to change the education system from halaqah to madrasa, organizing the place of study with a classroom system, using classical books as the main learning source, adding general subjects such as arithmetic, natural sciences and so on. Among the legacies of figures who contributed greatly to Islamic education in Minangkabau are Sumatra Tawalib Padang Panjang, Adabiah School, Diniyah Putri Padang Panjang, and MTI Canduang. It is hoped that the results of this research will be able to guide progress in the field of education, especially Islamic education in Minangkabau, then this research is also expected to be able to become a reference and benchmark for further research on different topics.